Powers - Le Guin, Ursula K., 1929- (Le Guin, Ursula K., 1929- Annals of the western shore., 2007)
A tragedy sets Gavir, a young slave, on a dangerous road to freedom and dealing with the powers he has hitherto kept secret, including the ability to see flashes of the future.